Conditional Deletion of Smad1 Ameliorates Glomerular Injury in Progressive Glomerulonephritis - Araki, Makoto; Matsubara, Takeshi; Abe, Hideharu; Torikoshi, Kazuo; Mima, Akira; Iehara, Noriyuki; Fukatsu, Atsushi; Kita, Toru; Arai, Hidenori; Doi, Toshio (Scientific reports, 2016)
Matrix expansion and cell proliferation are concomitantly observed in various glomerular injuries. However, the molecular mechanisms responsible for these changes have not been fully elucidated. We have reported that Smad1 is a key signalling molecule that regulates the transcription of type IV collagen (Col4) in mesangial matrix expansion and is thereby involved in glomerular injury in an acute model of glomerulonephritis. In this study, we addressed the role of Smad1 signalling in accelerated nephrotoxic nephritis (NTN), a model of progressive glomerulonephritis, using conditional deletion of Smad1 in Rosa26CreERT2 mice ( Smad1 -CKO). Mesangial matrix expansion in the Smad1 -CKO mice with NTN was significantly inhibited compared with that in wild type mice with NTN, which was consistent with the decrease in Col4 expression level. On the other hand, STAT3 activation and cell proliferation were not influenced by Smad1 deletion in the NTN model. Therefore, we investigated another factor that activates cell proliferation in the absence of Smad1. Id2 induced VEGF secretion and subsequent STAT3 activation, independently of Smad1 expression in mouse mesangial cells. Here we show that Smad1 plays an important role in the development of glomerular injury without affecting cell proliferation, in progressive glomerulonephritis.